Beatriz v. El Salvador: a loss for eugenic & health grounds for abortion in international human rights law - Castaldi, Ligia (Chrześcijaństwo-Świat-Polityka, 2025)
Beatriz v. El Salvador is an international judgment issued in December 2024 by the Inter-American Court of Human Rights involving a claim against El Salvador’s abortion ban. The Inter-American Court is an international tribunal with jurisdiction over most Latin American and Caribbean countries including El Salvador that oversees enforcement of the American Convention on Human Rights. The treaty contains a unique provision that establishes a “right [to life of every person to] be protected by law and, in general, from the moment of conception”. That provision has been repeatedly challenged in cases against Costa Rica and El Salvador. Beatriz is the latest judgment in that line of cases. Poised to become the regional court’s first abortion ruling, Beatriz v. El Salvador challenged El Salvador’s full ban on induced, elective abortion, similar to that of eight other Latin American and Caribbean states parties to the Convention. The case was litigated by the Inter-American Commission on Human Rights in conjunction with abortion advocacy organizations for more than a decade, leading to a mixed decision by the Inter-American Court that endorsed a progressive interpretation of the right to health and the concept of obstetric violence, but stopped short of creating abortion rights in the American Convention.